The range of the golden-mantle tamarin, Saguinus tripartitus (Milne Edwards, 1878): distributions and sympatry of four tamarin species in Colombia, Ecuador, and northern Peru - Rylands, Anthony B. (Springer Japan, 2010)
A detailed understanding of the range of the golden-mantle tamarin, Saguinus tripartitus (Milne Edwards, 1878), in Amazonian Peru and Ecuador is of particular relevance, not only because it is poorly known but also because it was on the basis of its supposed sympatry with the saddleback tamarin (S. fuscicollis lagonotus) that Thorington (Am J Primatol 15:367–371, 1988) argued that it is a distinct species rather than a saddleback tamarin subspecies, as was believed by Hershkovitz (Living new world monkeys, vol I. The University of Chicago Press, Chicago, 1977). A number of surveys have been carried out since 1988 in the supposed range of S. tripartitus, in both Ecuador and Peru. Here we summarize and discuss these issues and provide a new suggestion for the geographic range of this species; that is, between the ríos Napo and Curaray in Peru and extending east into Ecuador. We also review current evidence for the distributions of Spix’s black-mantle tamarin (S. nigricollis nigricollis), Graells’ black-mantle tamarin (S. n. graellsi), and the saddleback tamarin (S. fuscicollis lagonotus), which are also poorly known, and examine the evidence regarding sympatry between them. We conclude that despite the existence of a number of specimens with collecting localities that indicate overlap in their geographic ranges, the fact that the four tamarin species are of similar size and undoubtedly very similar in their feeding habits militates strongly against the occurrence of sympatry among them.